Work-Related Mental Health Issues in Graduate Student Population - Gallea, José Ignacio; Medrano, Leonardo Adrián; Morera, Luis Pedro (Frontiers in Neuroscience, 2021)
The scientific and educational community is becoming increasingly aware of the impact of current academic working conditions on graduate students’ mental health and how this is affecting scientific progress and ultimately society as a whole. Our study aimed to shed light on the work-related mental health issues affecting graduate students, providing a comprehensive research work including psychological and biological assessment. Our findings showed that a sizeable number of graduate student present anxiety, depression, or high burnout and that the time spent in academia plays an important role. The graduate student population displayed a specific work-related mental health issues profile with an altered hypothalamic–pituitary–adrenal (HPA) axis and low levels of work engagement. Finally, graduate students were equally stressed, with less work engagement, and more anxious and depressed than general workers.